Pengaruh Pijat Oksitosin Terhadap Produksi ASI Pada Ibu Pekerja Di Wilayah Kerja Puskesmas Sungai Raya Dalam Kabupaten Kubu Raya - Indri Erwhani; Sufiana; Hidayah; Sri Ariyanti (Jurnal Indragiri Penelitian Multidisiplin, 2022)
Background: Mother's milk (ASI) is the most perfect, practical, cheap and clean baby food because it is drunk directly from the mother's breast. Breast milk production is influenced by internal and external factors. Efforts that can be made by mothers and families to exclusively breastfeed and increase milk production are by optimizing the production of the hormone oxytocin, one of the things that mothers can do after giving birth is oxytocin massage. Oxytocin massage is a massage along the spine (vertebrae to the fifth-sixth rib). Oxytocin massage was performed on postpartum mothers with a duration of 3 minutes and the frequency of giving massage 2 times a day. Objective: To analyze the effect of oxytocin massage on breast milk production for working mothers in the working area of ​​Sungai Raya Dalam Public Health Center, Kubu Raya Regency. Research method: Quasi-experimental design pre-test and post-test nonequivalent controls group. The sampling technique used consecutive sampling technique by using 24 research respondents. The data analysis used was univariate bivariate analysis using the Wilcoxon-test. Results: After measuring milk production before and after oxytocin massage on working mothers with the Wilcoxon-test test, the p-value is 0.000 <0.05, so it can be concluded that there is a significant difference between breast milk production before and after being given oxytocin massage. Conclusion: There is a difference in the average milk production before and after oxytocin massage for working mothers in the Sungai Raya Dalam Public Health Center in Kubu Raya Regency.